Cold seep and oxygen minimum zone associated sources of margin heterogeneity affect benthic assemblages, diversity and nutrition at the Cascadian margin (NE Pacific Ocean) - Guilini, K; Levin, L A; Vanreusel, A (Progress in Oceanography, 2012)
Hydrate Ridge (HR), located on the northeastern Pacific margin off Oregon, is characterized by the presence of outcropping hydrates and active methane seepage. Additionally, permanent low oxygen conditions overlay the benthic realm. This study evaluated the relative influence of both seepage and oxygen minima as sources of habitat heterogeneity and potential stress-inducing features on the bathyal metazoan benthos (primarily nematodes) at three different seep and non-seep HR locations, exposed to decreasing bottom-water oxygen concentrations with increasing water depth. The nematode seep communities at HR exhibited low diversity with dominance of only one or two genera (Daptonema and Metadesmolaimus), elevated average individual biomass and $δ$13C evidence for strong dependance on chemosynthesis-derived carbon, resembling deep-sea seeps worldwide. Although the HR seep habitats harbored a distinct nematode community like in other known seep communities, they differed from deep-sea seeps in well-oxygenated waters based on that they shared the dominant genera with the surrounding non-seep sediments overlain by oxygen-deficient bottom water. The homogenizing effect of the oxygen minimum zone on the seep nematode assemblages and surrounding sediments was constant with increasing water depth and concomitant greater oxygen-deficiency, resulting in a loss of habitat heterogeneity.
Keywords: HOV Alvin (Human Occupied Vehicle)